What should be added to 4 x square - 5 x y + 7 to get minus 3 x square + 4 x y - 5 ?
Answers
Answered by
10
Step-by-step explanation:
Let the expression be X
Then,
(4x² - 5xy + 7) + x = 3x² + 4xy -5
x = ( 3x² + 4xy - 5) - (4x² - 5xy + 7)
x = 3x² + 4xy - 5 - 4x² + 5xy - 7
x = -x² + 9xy - 12
There fore, the expression -x² + 9xy - 12 should be added to 4x² - 5xy + 7 to get 3x² + 4xy - 5
Answered by
2
x = 8xy+2-9xy^2
Step by step explanation
1st equation + x= 2nd equation
x = 2nd - 1st
x = answer
mark me as braineliest
Similar questions
Psychology,
5 months ago
Chemistry,
5 months ago
Math,
11 months ago
Physics,
1 year ago
Science,
1 year ago